Tourist Routes of the Wilno Voivodeship in the Interwar Period - Włodzimierz Gański (Jan Długosz University in Częstochowa, 2023)
The purpose of the study is to research the system of tourist routes of the Wilno Voivodeship in the 1920s and 1930s. To convey the intended study, historical-type methodology was applied. In the 1920s and 1930s, a large number of tourist routes were developed in the Wilno Voivode- ship, both for hiking and for trips favouring road, rail or water transport. These routes were quite diverse in subject matter and could satisfy a variety of tourist requests in organizing recreation: visiting historical and cultural heritage sites, relaxing on the shores of numerous water reservoirs, as well as rafting on large and small rivers of the region or walks and trips along them by river transport. Finally, based on the analysis of the available primary sources issued in the covered period, it could be stated that the 1920s and 1930s may be treated as a turning point in the de- velopment of tourism in the Wilno Voivodeship, at least in terms of the number and variety of tourist routes then functioning in the region. The presented study may constitute useful material for any further research devoted to the history of tourism in Poland, Lithuania and Belarus.